In the shadow of policy : everyday practices in South African lan d and agrarian reform - Hebinck, Paulus Gerardus Maria, 1953-; Cousins, Ben, 1949- (Johannesburg, South Africa : Wits University Press, 2013)
"Notions of land and agrarian reform are now well entrenched in post -apartheid South Africa. But what this reform actually means for everyd ay life is not clearly understood, nor the way it will impact on the p olitical economy. In the Shadow of Policy explores the interface betwe en the policy of land and agrarian reform and its implementation; and between the decisions of policy 'experts' and actual livelihood experie nces in the fields and homesteads of land reform projects. Starting wit h an overview of the socio-historical context in which land and agraria n reform policy has evolved in South Africa, the volume presents empir ical case studies of land reform projects in the Northern, Western and Eastern Cape provinces. These draw on multiple voices from various se ctors and provide a rich source of material and critical reflections to inform future policy and research agendas. In the Shadow of Policy wil l be a key reference tool for those working in the area of development studies and land policy, and for civil society groups and NGOs involve d in land restitution." -- Back cover.
Includes bibliographical references and index.
Keywords: Land tenure -- South Africa. -- Government policy; Land reform -- Government policy -- South Africa; Commons -- South Africa. -- Government policy; Right of property. -- Government policy -- South Africa; Restitution. -- Government policy -- South Africa; Agriculture -- Government policy; Land use, Rural -- Government policy; Rural development. -- Government policy